PENGARUH ROA, EPS DAN DER TERHADAP RETURN SAHAM SYARIAH YANG LISTING DI INDEKS SAHAM SYARIAH INDONESIA (ISSI) (Periode 2021-2023): PENGARUH ROA, EPS DAN DER TERHADAP RETURN SAHAM SYARIAH YANG LISTING DI INDEKS SAHAM SYARIAH INDONESIA (ISSI) (Periode 2021-2023) - Hafid; Anselah, Suman; Hakim, Miftahur Rahman (Robust: Research of Business and Economics Studies, 2025)
This study aims to determine the effect of Return On Asset (ROA), Earning per Share (EPS), and Debt to Equity Ratio (DER) on the Return of Sharia Stocks Listed on the Indonesian Sharia Stock Index (ISSI) in 2021-2023 both partially and simultaneously. This study uses a quantitative approach. The population in this study were 61 infrastructure sector companies. The sample of this study used purposive sampling with 19 companies that met the criteria and 57 samples were obtained using panel data. The data analysis used was descriptive analysis, multiple linear regression and hypothesis testing. The results of the study indicate that: ROA has a significant effect on stock returns, this shows that the higher the ROA value, the greater the stock returns generated, because ROA indicates how efficient the company is in utilizing its assets to generate profits. EPS has a significant negative effect on stock returns, which means that when EPS increases, its stock returns actually decrease. DER does not have a significant effect on stock returns, this is because DER which reflects the company's capital structure does not always reflect stock market performance directly. And ROA, EPS and DER together affect stock returns. Which means that if viewed simultaneously, the three variables can explain or influence the rise and fall of stock returns.